EVALUATING THE MOTOR COMPETENCE OF HEARING-IMPAIRED PRIMARY SCHOOL STUDENTS - Mirela Hristova (Scientific Publishing House. NSA Press, 2019)
Motor Competence (MC) is the ability to perform a wide range of motor activities, relying on adequate levels of motor coordination and physical capacity to achieve. The aim of this study was to assess the development of basic motor competence indicators among students with hearing impairment aged 7 to 11 years. The research was done among a total of 91 children aged 7 to 11 years, of whom 42 children with hearing impairment (14 girls, 28 boys) and 49 - with non-impaired hearing (26 girls, 23 boys). For the purpose of the study, the Kiphard and Schilling battery test - Körperkoordinations Test für Kinder (KTK, 1974) was used. It consists of 4 tests that were measured once. Based on these, four motor quotients were formed, which in turn formed the so-called "Gross Motor Quotient". The results were processed statistically through variation and correlation analysis with the SPSS program. The results showed significantly lower development of motor competence among students with hearing impairment. The standardized motor quotients of the 4 tests (for boys - all 4; for girls - 3) and the total motor quotient were significantly lower than those of their hearing peers. The lack of significant differences in the mean values of the MQ3 in girls can be explained by the lower performance of the hearing girls compared to the KTK norms. As a conclusion, the motor competence of children with hearing impairment, assessed by both the overall motor quotient and the individual quotients obtained from the four tests is significantly lower than that of children with non-impaired hearing in primary school age.